2019
DOI: 10.1109/access.2018.2889304
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Laser-Based 3D SLAM for Coal Mine Rescue Robots

Abstract: An accurate description of laneway space with self-localization is a key issue when coal mine rescue robots (CMRRs) perform post-disaster exploration and rescue missions. The 3D simultaneous localization and mapping (SLAM) is an effective but time-critical and highly challenging task in complex laneway scenarios, especially after disasters. In this paper, we propose a novel real-time 3D SLAM based on normally distributed transform (NDT) that employs pose graph optimization and loop closure to further improve m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 45 publications
(60 reference statements)
0
22
0
Order By: Relevance
“…Two-dimensional LiDAR-based SLAMs are more computationally efficient than 3D ones. However, due to the limited number of dimensions, they are not able to provide the estimation of the vehicle’s pose on uneven ground with six degrees of freedom (DOF) [ 46 ]. Additionally, with the limited number of features, it is hard for this type of algorithm to adapt to long laneways, which are highly similar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional LiDAR-based SLAMs are more computationally efficient than 3D ones. However, due to the limited number of dimensions, they are not able to provide the estimation of the vehicle’s pose on uneven ground with six degrees of freedom (DOF) [ 46 ]. Additionally, with the limited number of features, it is hard for this type of algorithm to adapt to long laneways, which are highly similar.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods to restore 3D information from 2D point clouds can be used. Nevertheless, it makes the configuration complicated [ 46 ]. Therefore, in this work, we focus on testing 3D SLAM algorithms, which provide a more accurate estimation of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…e light detection and ranging (LiDAR) technique is being increasingly used in the mining industry because of its excellent environment perception. Li et al [16] proposed the SLAM algorithm based on LiDAR, which could realize the remote control and automatic positioning of a mine rescue robot. Wu et al [17] examined the navigation during unmanned driving in a mine and realized the stable output of the tunnel map by using the SLAM algorithm based on LiDAR.…”
Section: Introductionmentioning
confidence: 99%
“…A previous CSIRO research effort related to the measurement of haul truck load volumes had demonstrated the efficacy of laser-scanning (lidar) technologies for industrial load monitoring [4], with the resulting system successfully commercialised for the case of mining haul trucks. Related research in the area of three-dimensional (3D) mapping within coal mines [5,6] has validated the application of laser-scanning sensors to the problem of volume estimation of coal targets. Accurate volume and/or surface area mapping of coal targets using lidar technology requires careful selection and configuration of measuring instruments combined with an effective algorithm to deal with complicating factors such as target aspect and related shadowing effects [7], vehicle motion [8], and alterations in vehicle velocity [9].…”
Section: Introductionmentioning
confidence: 99%